MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Niega Aryani; Filia Filia Prima Artharina (STKIP Subang, 2024)
This research aims to increase student activity in Pancasila education subjects using the problem based learning model in elementary schools. The type of research used is Kemmis & Taggart's classroom action research model. The subjects of this research were class 5D students at SD Negeri Rejosari 01 for the 2023/2024 academic year with a total of 27 students. The 27 students consisted of 12 male students and 15 female students. The data collection technique uses observation sheets and written tests, then quantitative and qualitative descriptive analysis is carried out from the data obtained. The application of the problem based learning model before the cycle was carried out resulted in an average learning outcome of 69%. After the cycle was held, the activeness value for cycle I was 72%, increasing in cycle II to 82%. Cognitive learning outcomes for class 5D increased from cycle I, achieving classical completeness, with a class average of 73.14 or 73%, an increase in cycle II to 85.55 or 86%. The conclusion of this research is that the applica-tion of the Problem Based Learning (PBL) learning model can improve learning outcomes in Pancasila education learning for class 5D students at SD Negeri Rejosari 01.